2016
DOI: 10.1177/0741713615624207
|View full text |Cite
|
Sign up to set email alerts
|

Vocationalism Varies (a Lot)

Abstract: To encourage adult participation in education and training, contemporary policy makers typically encourage education and training provision to have a strongly vocational (employment-related) character, while also stressing individuals' responsibility for developing their own learning. Adults' motivation to learn is not, however, purely vocational-it varies substantially, not only between individuals but between populations. This article uses regression analysis to explain motivation among 12,000 learners in fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…That participation in formal adult education varies within and between countries, and factors impacting who participates in formal adult learning are multifaceted, is well established in the literature (Boeren, 2009;Lee & Desjardins, 2021). However, the conclusions for these variations differ, with some arguing that national institutional settings matter while others suggesting that life course constraints are what influences participation decisions more than institutional arrangements (Blossfeld et al, 2014;Boeren & Holford, 2016;Bratsberg et al, 2020). These various lines of reasoning are linked to conceptions of whether formal adult learning plays a compensatory or "upskilling"role in people's lives.…”
Section: Participation In Formal Adult Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…That participation in formal adult education varies within and between countries, and factors impacting who participates in formal adult learning are multifaceted, is well established in the literature (Boeren, 2009;Lee & Desjardins, 2021). However, the conclusions for these variations differ, with some arguing that national institutional settings matter while others suggesting that life course constraints are what influences participation decisions more than institutional arrangements (Blossfeld et al, 2014;Boeren & Holford, 2016;Bratsberg et al, 2020). These various lines of reasoning are linked to conceptions of whether formal adult learning plays a compensatory or "upskilling"role in people's lives.…”
Section: Participation In Formal Adult Educationmentioning
confidence: 99%
“…While research on formalized HVE is varied in scope, the literature on how participation in formal adult education varies by individual characteristics or national contexts is a rich area we can learn from. For instance, studies have demonstrated how adult vocational motivations vary by gender in different ways, and that institutional contexts matter when disentangling these individual-level effects (Boeren & Holford, 2016). Earlier studies also show that age has been one of the strongest determining characteristics for participation, and that older workers participate less in continuing education and training (Blossfeld et al, 2014; Boeren et al, 2010; Desjardins et al, 2006).…”
Section: Participation In Formal Adult Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Yoon et al (2015) indicated that internship was the simulation process of college students attempting the career selection; students' work value of internship was the work value of a university' correct establishment of guidance for the basis of the future occupation intention. Boeren & Holford (2016) proposed that students' learning experience acquiring in the internship process would to some degree aff ect the learning outcome and work value of future employment. Pasban & Nojedeh (2016) stated that internship allowed a student directly acquiring a job and leaving deep impression to the potential employer to build the confi dence in seeking a job, enhance work value, and establish social skills, which would benefi t the future recruitment interview.…”
Section: Employabilitymentioning
confidence: 99%
“…The pressing demands for a more educated workforce caused by the global economy in the United States (Kallison, 2017) exist also in the European Union (EU) (Lundvall & Rasmussen, 2016). At the same time, the literature observes that in the area of Adult Learning and Education there is a trend consisting in favoring educational initiatives related to VET, due to its incidence in economic growth and competitiveness (Boeren & Holford, 2016), a similar phenomenon also observed in Spain (Lucio-Villegas, 2012). As a response to these phenomena, the EU established four objectives for education and training systems within the lifelong learning perspective, that the Member States (including Catalonia as part of Spain) should implement by 2020 and one of them is 'enhancing creativity and innovation, including entrepreneurship, at all levels of education and training' (European Council, 2009, p. 3).…”
Section: Introductionmentioning
confidence: 99%